Development of Android Applications as an Operating System Media for Learning Electronic Control Competencies in ClassXI students SMKN 2 Pengasih - Singgih Yuntoto (Jurnal Mandiri IT, 2021)
At this time the learning process by teachers rarely uses technology and learning media. Students have difficulty using learning media. The limitation of tools is an obstacle in accessing learning media. This research is a type of development research. The product development model adopts a software development model consisting of (1) software requirements analysis, (2) design, (3) code writing and (4) testing. Data collection techniques were carried out by observation, interviews and questionnaires. The testing phase is carried out with product validation by experts, testing on first users (teachers) and testing on end users (students). The data analysis technique used is descriptive analysis technique. The results of this study are: (1) the android application model for appropriate learning media on the competence of operating the electronic control system includes preparation, the subject matter of the operation of the electronic control system, and the evaluation model of choice questions; (2) test the functionality of the android application for appropriate learning media on the competence of operating an electronic control system including ease of navigation, application performance and ease of operation; (3) the feasibility of the android application for appropriate learning media on the competence of operating the electronic control system, based on the performance of the application it can run well. Based on the converted average assessment with a score range of 0-100, the score from media experts was obtained with a score of 83.33 in the "very feasible" category, the assessment by material experts with a score of 71.